2021
DOI: 10.3390/ph14090845
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycin D Arrests Cell Cycle of Hepatocellular Carcinoma Cell Lines and Induces p53-Dependent Cell Death: A Study of the Molecular Mechanism Involved in the Protective Effect of IRS-4

Abstract: Actinomycin D (ActD) is an FDA-approved NCI oncology drug that specifically targets and downregulates stem cell transcription factors, which leads to a depletion of stem cells within the tumor bulk. Recently, our research group demonstrated the importance of IRS-4 in the development of liver cancer. In this study, we evaluated the protective effects of IRS-4 against ActD. For this study, three hepatocellular carcinoma cell lines (HepG2, Huh7, and Chang cells) were used to study the mechanism of actinomycin D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…In myeloid progenitor cells, IRS-4 mediated AKT signaling after insulin stimulation without promoting an anti-apoptotic effect [ 69 ]; however, in pancreatic β-cells (INS-1 cells), IRS4 introduction compensated for the apoptosis induced by a decrease in the IRS2 level [ 70 ]. Some studies suggested that IRS4 overexpression in tumor cells makes them more resistant to treatment with trastuzumab and lapatinib [ 23 ], as well as actinomycin D [ 71 ]. It has recently been shown that IRS4 exerts an effect on tumor cell migration, a very important aspect of tumor growth and metastasis formation.…”
Section: Resultsmentioning
confidence: 99%
“…In myeloid progenitor cells, IRS-4 mediated AKT signaling after insulin stimulation without promoting an anti-apoptotic effect [ 69 ]; however, in pancreatic β-cells (INS-1 cells), IRS4 introduction compensated for the apoptosis induced by a decrease in the IRS2 level [ 70 ]. Some studies suggested that IRS4 overexpression in tumor cells makes them more resistant to treatment with trastuzumab and lapatinib [ 23 ], as well as actinomycin D [ 71 ]. It has recently been shown that IRS4 exerts an effect on tumor cell migration, a very important aspect of tumor growth and metastasis formation.…”
Section: Resultsmentioning
confidence: 99%
“…PcoS is one of the most common hormonal disorders of women during the reproductive years. in patients with PcoS, the mitochondrial state of Gcs is altered, the spindle assembly disordered, and the quality of oocytes decreases (15)(16)(17). any problems of Gcs in growth differentiation, metabolism and apoptosis will directly or indirectly affect the quality of follicular (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…A similar cleavage-inhibiting effect of actinomycin D was documented in previous studies on in vitro cultured mouse, rabbit and bovine oocytes 10,29,30 , developing preimplantation embryos 31 and blastocysts 15,32 . Actinomycin D at nanomolar concentrations also inhibited proliferation in various cell lines and tissues 33,34 .…”
Section: Response Of Embryonic Phagocytes To Increased Incidence Of A...mentioning
confidence: 97%